2007
DOI: 10.1121/1.2722213
|View full text |Cite
|
Sign up to set email alerts
|

Wideband ipsilateral measurements of middle-ear muscle reflex thresholds in children and adults

Abstract: The goals of the current study were to: 1) evaluate the feasibility of a new wideband approach to measuring middle-ear muscle reflex (MEMR) status, and 2) to test the hypothesis that ipsilateral thresholds elicited with 1 or 2 kHz tones and broadband noise activators on a wideband acoustic transfer function (WATF) system are lower than thresholds elicited on a clinical system. Clinical MEMR tests have limitations, including the need for high activator levels to elicit a shift in a narrowband probe (e.g., a 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 32 publications
6
36
0
1
Order By: Relevance
“…The subject inclusion criteria and age range in this SFOAE study were similar to those in the acoustic transferfunction data set measured in the subjects tested by Schairer et al (2007). Specifically, subjects were included in the SFOAE study only if their air-conduction thresholds were 15 dB HL or better at half-octave frequencies from 0.25 to 8 kHz, and air-bone gaps were 10 dB or less at frequencies from 0.25 to 4 kHz.…”
Section: Interpreting Suppression Of Sfoaes At High Frequenciesmentioning
confidence: 96%
See 1 more Smart Citation
“…The subject inclusion criteria and age range in this SFOAE study were similar to those in the acoustic transferfunction data set measured in the subjects tested by Schairer et al (2007). Specifically, subjects were included in the SFOAE study only if their air-conduction thresholds were 15 dB HL or better at half-octave frequencies from 0.25 to 8 kHz, and air-bone gaps were 10 dB or less at frequencies from 0.25 to 4 kHz.…”
Section: Interpreting Suppression Of Sfoaes At High Frequenciesmentioning
confidence: 96%
“…The aural acoustic transfer functions analyzed in the present report were measured between 0.22 and 8 kHz in the same group of normal-hearing subjects who participated in a study reported by Schairer et al (2007). Summarizing the inclusion criteria described in greater detail by Schairer et al, an ear test was included in the database based on normal otoscopy, normal 0.226-kHz tympanometry, and normal audiometric thresholds, i.e., air-conduction thresholds 15 dB hearing level (HL) between 0.5 and 8 kHz, and airbone gaps 15 dB between 0.5 and 4 kHz.…”
Section: B Acoustic Transfer-function Measurementsmentioning
confidence: 99%
“…First, unlike the MOC, we are not aware of any neural-reflex circuitry that could mediate differential MER activity under different states of attention. Second, our most important measurements were made at 4.0 kHz, and the MER primarily attenuates lower frequencies (Dallos, 1973;Goodman and Keefe, 2006;Henin et al, 2014;Schairer et al, 2007). Third, there are large individual differences in the SPLs that activate the MER (e.g., Goodman and Keefe, 2006;Henin et al, 2014), and when a 4.0-kHz tone of 80 dB was presented during the initial screening of these subjects, only three had an MER.…”
Section: F Possible Alternative Explanationsmentioning
confidence: 99%
“…In the most commonly used condition, the noise levels were 63 and 69 dB SPL for the single-earphone and two-earphone presentations of each triplet, respectively, the larger of which is close to the nominal MER threshold for broadband noise ͑Wilson and Margolis, 1999͒. In adult ears, Shairer et al ͑2007͒ found that the range of broadband noise levels capable of eliciting a statistically significant change in acoustic admittance in the ear canal was 64-80 dB Hearing Level. These facts make it logically possible that some or all of the effects reported here were attributable to the MER rather than to cochlear mechanisms and the MOC system.…”
mentioning
confidence: 99%
“…We are not unequivocally able to rule out a potential influence of the MER on our nSFOAE measures, but several facts suggest that those influences were minimal. ͑1͒ The MER primarily acts to attenuate the transmission of low frequencies through the middle ear ͑Dallos, 1973; Goodman and Keefe, 2006;Shairer et al, 2007͒. In the present study, the frequency of the probe tone and the frequency at which the nSFOAE was measured was 4.0 kHz. Shairer et al ͑2007͒ found that above 2.0 kHz, shifts in acoustic admittance were not significantly different from zero for any level of noise activator.…”
mentioning
confidence: 99%